5(2(4)-7)-3(3(4)-10)+4=

Simple and best practice solution for 5(2(4)-7)-3(3(4)-10)+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2(4)-7)-3(3(4)-10)+4= equation:


Simplifying
5(2(4) + -7) + -3(3(4) + -10) + 4 = 0

Multiply 2 * 4
5(8 + -7) + -3(3(4) + -10) + 4 = 0

Combine like terms: 8 + -7 = 1
5(1) + -3(3(4) + -10) + 4 = 0

Multiply 5 * 1
5 + -3(3(4) + -10) + 4 = 0

Multiply 3 * 4
5 + -3(12 + -10) + 4 = 0

Combine like terms: 12 + -10 = 2
5 + -3(2) + 4 = 0

Multiply -3 * 2
5 + -6 + 4 = 0

Combine like terms: 5 + -6 = -1
-1 + 4 = 0

Combine like terms: -1 + 4 = 3
3 = 0

Solving
3 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 14+16=16+n | | 12(x+5)=13y+2 | | 4i+19=-13 | | tablefory=3x-2 | | 63=x+(x-7) | | 15.5+(3.5+10)=(15.5+n)+10 | | 6x-5y-30=0 | | 2y+-7=13 | | D=110-30 | | -28x+-5= | | 6h-3=-9 | | -15v+9=-20v-9 | | 10p-45=3(b-15) | | 58454+n=58454 | | 7g+9=44 | | (x)(4x)=192 | | 3x-21+5x=16+6x-11 | | 2a-3b+1=0 | | 3f-27=-3 | | 3y-6=18-y | | 4x-2x(4+6)=-22 | | 4.9t^2+4t-50=0 | | 8e+5=21 | | 6(z-4)=12 | | 4x+9y+3(x+y)= | | 2/3x+4=7/3x-12 | | 3d+7=-11 | | 72=8(s-2) | | 2x=7x+5 | | 72=8(-2) | | 2k+21=35 | | 4secx+9=0 |

Equations solver categories